Budaya Maritim dalam Cerpen Kutukan Keturunan Bajak Laut Karya Bagus Sulistio Sebagai Materi Pengenalan Budaya BIPA - Fatma Anggita Putri (Pencerah, 2022)
This study aims to explain and describe the cultural elements contained in an Indonesian short story entitled Kutukan Keturunan Bajak Laut by Bagus Sulistio as Indonesian language teaching material for Foreign Speakers (BIPA) level C1 and C2. The subject of this research is a short story entitle Kutukan Keturunan Bajak Laut by Bagus Sulistio. This study uses a qualitative descriptive approach to systematically describe phenomena, namely cultural elements as BIPA teaching materials. Data collection techniques used reading-note techniques, literature study, and data cards. This research shows that the short story Kutukan Keturunan Bajak Laut by Bagus Sulistio contains cultural elements in the form of language, knowledge system, livelihood system, religious system and art. Elements of culture can be used as teaching materials or as an introduction to culture, especially maritime culture as a support for the language skills of BIPA teachers.